ERRORS ANALYSIS OF JAPANESE SENTENCE WRITING IN SAKUBUN BY CLASS 25A STUDENTS UNTAG SEMARANG - Septa Wiki Dwi Cahyani (LINGUAMEDIA Journal, 2025)
This study aims to analyze the types of errors and the factors causing errors in Japanese sentence writing (sakubun) produced by Class 25A students of the D3 Japanese Language Study Program at Universitas 17 Agustus 1945 Semarang. The study used a descriptive qualitative method. The research data were obtained from students’ handwritten sakubun assignments on the theme of family and supported by questionnaire responses from 24 students. Data analysis was conducted using language error analysis procedures proposed by Corder and Tarigan, which include data collection, error identification, error classification, error explanation, and error evaluation. Questionnaires were used to identify the factors underlying the writing errors. The results show that three main types of errors were found in students’ sakubun writing: vocabulary writing errors, sentence pattern usage errors, and particle usage errors. The most dominant errors occurred in sentence patterns and particle usage, indicating that students still experience difficulties in mastering basic Japanese grammatical structures. Vocabulary errors were mainly caused by inaccuracies in hiragana writing, while sentence pattern errors were related to inconsistent speech levels and limited understanding of grammatical constructions. Particle usage errors reflect students’ insufficient mastery of particle functions in sentence construction. Furthermore, the questionnaire results indicate that these errors are influenced by limited kanji proficiency, restricted vocabulary, interference from Indonesian, insufficient writing practice, and a lack of detailed instructor feedback. Overall, the findings suggest that both linguistic and pedagogical factors play important roles in students’ sakubun writing performance.